Gaps in Constitutional Protection of Land Rights Due to Coastal Erosion: Celah Perlindungan Konstitusional atas Hak Tanah Akibat Abrasi Laut - Siti Aura Fadhillah; Mia Hadiati (Indonesian Journal of Law and Economics Review, 2026)
General Background Property ownership is a fundamental constitutional concern within the rule of law and welfare state framework. Specific Background Coastal abrasion can permanently eliminate physical land, causing environmental damage and legal uncertainty for communities whose ownership depends on the existence of land as a legal object. Knowledge Gap Existing regulations have not fully resolved uncertainty regarding land status, compensation mechanisms, and state responsibility for restoring affected community rights. Aims This study analyzes the urgency of fulfilling citizens’ constitutional rights in protecting land ownership affected by coastal abrasion. Results The study finds that the state has a constitutional obligation to provide preventive and remedial legal protection through coastal management policies, mitigation, compensation, relocation, and legal certainty regarding land ownership. Novelty The study positions land loss caused by abrasion as an urgent constitutional issue rather than only an environmental or agrarian problem. Implications Comprehensive legal policy is required to realize justice, legal certainty, and community welfare. Highlights: Physical disappearance of parcels creates uncertainty over ownership status. Affected communities require compensation, relocation, mitigation, and restoration mechanisms. State responsibility remains central to justice and welfare. Keywords: Constitutional Rights, Coastal Erosion, Land Ownership Rights, Legal Protection, Welfare State.